Cadre's Ability to use Android-Based Stunting Prevention Applications - Siti Musyarofah; Livana PH; Novi Indrayati; Setianingsih Setianingsih (GLOBAL HEALTH SCIENCE GROUP, 2022)
Stunting is a form of malnutrition which is measured based on the 2005 WHO standard deviation. Stunting can be assessed by measuring the height and age of H/A according to the WHO child growth standard, that is, if the z-score H/A is <-2 SD . Health cadres need an application to make it easier to record, report, and prevent stunting. This study was to determined the effectiveness of the ability of cadres to use android-based applications for stunting prevention. This study used a quantitative study with a quasi-experimental design using a pre post test without a control group. The sample of this research is health cadres in Banyubiru Village and Ambarawa District, Semarang Regency, Central Java with a total sample of 120 respondents used purposive sampling technique. The research instrument used a questionnaire. Our bivariate data analysis ed Wilcoxon test. The results showed that there was an increase in the ability of cadres to use android-based stunting prevention applications, with a p value of 0.0001. cadres who have wanted the application need to be continuously empowered, and the use of the application can be used continuously.